CD3 aptamers promote expansion and persistence of tumor-reactive T cells for adoptive T cell therapy in cancer - Ashwathi Puravankara Menon; Helena Villanueva; Daniel Meraviglia-Crivelli; Hisse M. van Santen; Joschka Hellmeier; Angelina Zheleva; Francesca Nonateli; Timo Peters; Tassilo L.A. Wachsmann; Mercedes Hernandez-Rueda; Johannes B. Huppa; Gerhard J. Schütz; et al. (Elsevier, 2024)
The CD3/T cell receptor (TCR) complex is responsible for antigen-specific pathogen recognition by T cells, and initiates the signaling cascade necessary for activation of effector functions. CD3 agonistic antibodies are commonly used to expand T lymphocytes in a wide range of clinical applications, including in adoptive T cell therapy for cancer patients. A major drawback of expanding T cell populations ex vivo using CD3 agonistic antibodies is that they expand and activate T cells independent of their TCR antigen specificity. Therapeutic agents that facilitate expansion of T cells in an antigen-specific manner and reduce their threshold of T cell activation are therefore of great interest for adoptive T cell therapy protocols. To identify CD3-specific T cell agonists, several RNA aptamers were selected against CD3 using Systematic Evolution of Ligands by EXponential enrichment combined with high-throughput sequencing. The extent and specificity of aptamer binding to target CD3 were assessed through surface plasma resonance, P32 double-filter assays, and flow cytometry. Aptamer-mediated modulation of the threshold of T cell activation was observed in vitro and in preclinical transgenic TCR mouse models. The aptamers improved efficacy and persistence of adoptive T cell therapy by low-affinity TCR-reactive T lymphocytes in melanoma-bearing mice. Thus, CD3-specific aptamers can be applied as therapeutic agents which facilitate the expansion of tumor-reactive T lymphocytes while conserving their tumor specificity. Furthermore, selected CD3 aptamers also exhibit cross-reactivity to human CD3, expanding their potential for clinical translation and application in the future.